2013
DOI: 10.1177/1040638713486112
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A as a prognostic marker in cats with various diseases

Abstract: Serum amyloid A (SAA) is reported not only as a marker for the presence of inflammation but also as a prognostic indicator in human beings. In cats, however, there is no report on the association between SAA concentration and prognosis. The objective of the current study was to evaluate SAA concentration as a prognostic marker in diseased cats. A total of 175 cats with neoplastic diseases, inflammatory diseases, and other diseases were retrospectively recruited, and the medical records of these cats, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 16 publications
3
60
0
Order By: Relevance
“…8,41,42 Furthermore, development of an APP response and of oxidative stress were previously described in human breast cancer and in canine mammary tumours. [21][22][23][24][25][26] APP and parameters of oxidative status were also proved to be clinically useful biomarkers in feline oncologic diseases, [43][44][45] however, to the best of our knowledge, this is the first study to comprehensively evaluate the APP and the antioxidant responses of feline spontaneous malignant mammary tumours.…”
Section: Discussionmentioning
confidence: 99%
“…8,41,42 Furthermore, development of an APP response and of oxidative stress were previously described in human breast cancer and in canine mammary tumours. [21][22][23][24][25][26] APP and parameters of oxidative status were also proved to be clinically useful biomarkers in feline oncologic diseases, [43][44][45] however, to the best of our knowledge, this is the first study to comprehensively evaluate the APP and the antioxidant responses of feline spontaneous malignant mammary tumours.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, AGP in cat serum or effusion samples is a recognised biomarker of FIP (6,21,25). However, these APP concentrations increase not only in inflammatory diseases, but also in several non-inflammatory disorders, such as neoplasia, diabetes mellitus and hyperthyroidism (10,22,27). In the present study, changes in APPs in cats with anaemia were investigated.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of SAA and AGP concentrations are considered useful in detecting the presence of inflammation (17,26,27). In addition, AGP in cat serum or effusion samples is a recognised biomarker of FIP (6,21,25).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a study suggested that the median survival time of cats with elevated SAA levels (>0.82 mg/L) was signifi cantly shorter in various diseases, including FIP [8].…”
Section: Catsmentioning
confidence: 99%
“…Recently, this protein has been investigated as a signifi cant prognostic marker and as a useful predictive indicator of prognosis in various diseases [7][8][9][10]. An isoform of SAA (SAA-2) is involved in reactive amyloidosis and other chronic infl ammatory diseases.…”
Section: Introductionmentioning
confidence: 99%